Improving Learning Achievement Using the Game-Assisted Method 'Wordwall' in Writing Advertisement Texts 'Pariwara' - Utomo, Tri Duto; Handayani, Dwi; Mujimin, Mujimin (Centre for Literary and Cultural Studies, 2024)
This study aimed to describe the implementation of Javanese language learning activities and determine the improvement of learning achievement in writing advertisement/advertisement texts with the Wordwall media-assisted game method. The primary problem for students is the limited Javanese vocabulary, which causes low learning achievement. The research method used in this study is classroom action research (CAR), which details two cycles. Techniques for collecting data include observation, assessment, and documentation techniques. The study's results showed a significant increase in students' writing skills. In cycle one, around 38.24% of students achieved a score of ≥ 75; in the second cycle, it increased to 70.59%. Wordwall learning media has proven effective, reducing the incomplete percentage from 61.76% in cycle one to 29.41% in the second cycle. This study concluded that the Wordwall media-assisted game method could be an alternative in dealing with problems in Javanese language subjects, significantly improving writing skills in advertisement/advertisement texts. This research also contributes to developing innovative Javanese language learning methods to improve writing skills by integrating Wordwall to address learners' interests and Javanese vocabulary limitations.